The Function of SIM in The Industry of Education (Zenius.Net) - Faeni, Dewi Puspaningtyas; Salsabilla, Naura (LANCAH: Jurnal Inovasi dan Tren, 2024)
Education around the world has experienced a significant decline due to information technology. As a result, traditional or conventional teaching methods are not very effective due to time and resource constraints. Furthermore, information technology has made new teaching methods dubbed E-Learning methods available. The electronic learning system, often known as e-learning in English or electronic learning, is a new approach to the learning process. E-learning is the foundation and logical consequence of the rapid advancement of information and communication technologies. With e-learning, students (or learners, if you will) no longer need to sit through classroom lectures in order to fully comprehend each lesson that a teacher teaches them. E-learning has the potential to increase learning objectives and, at the very least, reduce costs that must be covered by academic or training programs.